2019
DOI: 10.2147/ott.s217041
|View full text |Cite
|
Sign up to set email alerts
|

<p>RASSF6 Is Downregulated In Human Bladder Cancers And Regulates Doxorubicin Sensitivity And Mitochondrial Membrane Potential Via The Hippo Signaling Pathway</p>

Abstract: BackgroundThe present study aimed to investigate the clinicopathological significance and biological roles of RASSF6 in human bladder cancers.Materials and methodsImmunohistochemistry and Western blots were used to examine the protein expression of RASSF6 in bladder cancer tissues. Biological roles of RASSF6 were examined using MTT, colony formation assay, Matrigel invasion assay, cell cycle analysis, AnnexinV/PI staining and JC-1 staining. Western blot analysis was used to examine the potential mechanism.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…In senescent tumor cells, YAP sustains expression of the anti-apoptotic factor survivin [ 159 ]. YAP activates expression of BCL-xL in bladder cancer, and depletion of YAP increases apoptosis [ 160 ]. Using a hybrid spheroid model of cell competition, Liu et al showed that glioblastoma cells express YAP heterogeneously, and YAP-low cells experience more apoptosis, reminiscent of the E4.5 mouse epiblast, though it is not specified what downstream targets are involved [ 161 ].…”
Section: Yap/taz and Apoptosis In Cancermentioning
confidence: 99%
“…In senescent tumor cells, YAP sustains expression of the anti-apoptotic factor survivin [ 159 ]. YAP activates expression of BCL-xL in bladder cancer, and depletion of YAP increases apoptosis [ 160 ]. Using a hybrid spheroid model of cell competition, Liu et al showed that glioblastoma cells express YAP heterogeneously, and YAP-low cells experience more apoptosis, reminiscent of the E4.5 mouse epiblast, though it is not specified what downstream targets are involved [ 161 ].…”
Section: Yap/taz and Apoptosis In Cancermentioning
confidence: 99%
“…The tumor suppressor RASSF6 (another member in the RASSF family, along with RASSF1A), which is frequently downregulated in bladder cancer, regulates doxorubicin sensitivity via the Hippo pathway [ 95 ]. RASSF6 overexpression augments doxorubicin-triggered cell apoptosis by negatively regulating YAP and the pro-apoptosis protein Bcl-xL.…”
Section: Hippo Signaling Pathway-mediated Drug Resistancementioning
confidence: 99%
“…Allen et al identified RASSF6 based on the homology with RASSF1 and reported it as a putative tumor suppressor (Allen et al, 2007). The studies of cancer patients support its tumor suppressive role in human cancers (Djos et al, 2012;Guo et al, 2016;Hesson et al, 2009;Liang et al, 2014;Mezzanotte et al, 2014;Richter et al, 2009;Tan et al, 2019;Wen et al, 2011;Ye et al, 2015;Younesian et al, 2019). The experiments using human cancer cell lines show that RASSF6 is involved in the regulation of p53, RB1 and the tumor suppressor Hippo pathway (Hossain et al, 2018;Ikeda et al, 2009;Iwasa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%